Reviving the Remedy: Global Action against Antimicrobial Resistance through Stewardship - Samanta, Souman; Sah, Sneha (Indian Journal of Pharmacy Practice)
Antimicrobial Resistance (AMR) has become a significant healthcare problem worldwide, claiming an estimated 1.27 million lives in 2019, and the situation is projected to worsen by 2050. This threat arises from the improper use of antibiotics, particularly during surgeries and the treatment of common infections. Some of the mechanisms of bacterial resistance are drug target changes, enzyme breakdown, hampered absorption, and efflux of drugs, commonly aided by changes in genes through mutation or horizontal gene transfer. These translate into chronic infection, raised medical expenditure, long hospitalizations, and raised morbidity and mortality. Antimicrobial Stewardship Programs (ASPs) are a pillar in the fight against AMR because they provide direction in the rational use of antibiotics, audit prescriptions, place formulary restrictions, and endorse evidence-based measures. ASP implementation, however, in LMICs is hard because of a lack of infrastructure, low laboratory capacity, poor administrative management, and scarce interaction between healthcare professionals and the population. In addition to stewardship, the process of returning antibiotics’ efficacy needs international collaboration in antibiotics research, a reappraisal of pharmaceutical R&D, and an incentive to produce antibiotics. The global health community should work together to create a holistic defense against AMR so that future generations can still use life-saving drugs. Unless it is checked, AMR poses a risk of reversing decades of medical advances, as infections become more and more incurable and even more lethal.
Keywords: Antimicrobial Resistance (AMR); Antibiotic misuse; Bacterial resistance mechanisms; Antimicrobial Stewardship Programs (ASPs); Global collaboration